Impact of Covid-19 in Nursing Education: Literature Review - Zendrato, Mey Lona Verawaty; Hiko, Veronika Fernanda Dua (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Pandemic Covid 19 attack the world, this greatly impacts to nursing education. Method of online learning during the pandemic, affecting the quality of nursing education. Considering nursing not only has the achievement of knowledge, but competence becomes the core value that must be obtained by prospective professional nurses. The aims to describe the impact of online learning experienced. The method is literature review, used 7 articles according to the criteria. There were concerns in the learning that resulted in moderate anxiety levels – severe experienced by students, decreased motivation, ineffective learning quality, cooperation, communication and interaction decreased, clinical skills could not be achieved, the study period increased. Online learning cannot be seen as effectively evenly distributed in all regions, due to various factors such as electricity, internet connectivity, communication media and types of achievements according to the science. Support from educational institutions is needed to improve the capacity of educators